The effect of temperature on physiological energetics of a fast‐growing selective strain and a hatchery population of the Pacific oyster (Crassostrea gigas). (11th June 2018) - Zhang, Jingxiao; Li, Qi; Liu, Shikai; Yu, Hong; Kong, Lingfeng
Abstract: Growth is an important aquaculture trait, which has been one of the most important traits for genetic improvement in aquatic species. Numerous fast‐growing domesticated aquaculture organisms are being cultured, but the physiological processes underlying growth remain largely unexplored. The Pacific oyster ( Crassostrea gigas ) is one of the most widely farmed bivalves. In order to improve the productivity traits, a fast‐growing selective strain of C. gigas was established. In this study, we compared physiological energetics of the fast‐growing selective strain and an unselected hatchery population of C. gigas under different conditions of temperature. Components of energy gain (clearance rates, ingestion rates, absorption efficiency and absorption rates), energy loss (metabolic rates) and resulting energy budget (scope for growth) were analysed at four temperatures (15, 20, 25 and 30°C). The results indicated that selective breeding oysters had a higher energy gain compared to unselected oysters, but the selected strain and hatchery population of oysters did not significantly differ in metabolic rates at all tested temperatures ( p  >   0.05). The enhanced energy gain resulted in almost two times higher scope for growth in selective breeding oysters compared with unselected oysters. Physiological characteristics of C. gigas were greatly affected by temperature and showed a fluctuation with the increase in temperatures. The selective breeding oysters outperformed those of hatchery population in growth performance by an increased energy gain along with a similar energy loss. This study provided insight into physiological energetics accounting for growth improvements in fast‐growing selective strain of C. gigas .